Can you afford to retire? [videorecording (DVD)] - Young, Rick (PBS Video, 2006)
"The baby boomer generation is headed for a shock as it hits retirement: boomers will be long on life expectancy but short on income. In addition to Social Security, the pillars of retirement income for Americans have been either lifetime corporate pensions or employee-contribution plans such as 401Ks. But both retirement strategies are in trouble. Buffeted by pension cuts, corporate bankruptcies, and the 2001-2002 stock market crash, most boomers now expect to be working into their retirement years."--Container.